2013
DOI: 10.1177/0954407013502319
|View full text |Cite
|
Sign up to set email alerts
|

Active front-steering control of a sport utility vehicle using a robust linear quadratic regulator method, with emphasis on the roll dynamics

Abstract: One of the well-known methods for improving the lateral stability of a vehicle is to utilize an active steering controller. Common active steering systems use feedback signals from a yaw rate sensor and side-slip angle estimation. However, in some driving conditions, skilled drivers can prevent vehicle rollover using the steering angle of the vehicle. Hence, the effect of an active front-steering controller on the roll angle of the vehicle is studied in this paper. For this study, a three-degree-of-freedom lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The optimal value of the quadratic cost function (14) converges to = (0) T (0) (16) where ∈ ℝ × is the solution of the Lyapunov equation given by…”
Section: Lemma [21]mentioning
confidence: 99%
“…The optimal value of the quadratic cost function (14) converges to = (0) T (0) (16) where ∈ ℝ × is the solution of the Lyapunov equation given by…”
Section: Lemma [21]mentioning
confidence: 99%
“…In recent years, there have been a lot of researches aiming at enhancing roll stability through various techniques, such as active steering, 79 active braking, 10,11 active suspension, 1214 anti-roll bars 15,16 and combination of them. 1719 Imine et al 7 developed an active steering controller to avoid the rollover of heavy vehicles, experimental tests done in a real zigzag scenario showed that this approach was effective and could make it possible to control the vehicle and to avoid its rollover.…”
Section: Introductionmentioning
confidence: 99%
“…The vehicle control community is also highly interested in the rollover of vehicles, because it is one of the most frequently encountered situations in traffic accidents. Many approaches for preventing the vehicle rollover have been proposed, such as differential braking control (Solmaz et al, 2006; Yim, 2011; Yim et al, 2013; Yoon et al, 2007), active front wheel steering control (Elmi et al, 2013; Solmaz et al, 2007; Zhao et al, 2017), active rear steering control (Zhao et al, 2017), suspension control (Fakhraei et al, 2017; Sahin et al, 2007), drive torque control (Larish et al, 2013), and any combination of chassis control methods (Gaspar et al, 2004; Lu et al, 2012; March and Shim, 2007; Rahimi and Naraghi, 2017; Yoon et al, 2010). Mostly, studies in the literature use a rollover index to detect that the vehicle approaches the limits of rollover in real-time.…”
Section: Introductionmentioning
confidence: 99%